Representation of Power in the Symbolism of Traditional Rituals: Cultural Anthropology Studies in Eastern Indonesia - Yusriani, Yuyu (Mahogany Journal De Social, 2025)
This study challenges the depiction of power in the symbolic structure of traditional rituals in Eastern Indonesia through the perspectives of cultural anthropology. Rituals are viewed not only as spiritual practices or practices embedded in past traditions but as symbolic arenas where power relations, social authority, and collective personality are enacted. In traditional societies, authority is often enshrined in sacral signs- such as relics, hymns, or celebrations- each with a hierarchical meaning that restates authority. The data collection was conducted using qualitative ethnographic approach, where participant observations and in-depth interviews with traditional rulers, ritual experts, and community members involved in the ceremonies were utilized to collect data. The analytic emphasis was on deriving the meaning of ritual symbols and comparing them to the social power structures that survive. The results reveal that rituals are used as a means of justifying power of traditional leaders, maintaining social stratifications, and acting as means of social control. Symbolic analysis discloses that power is not only a result of political or economic status but also of spiritual legitimacy passed down through generations. At the same time, the new presence of women and youth is an indicator of negotiated authority and changing significances. Finally, power in the Eastern Indonesian societies is developed through symbolic formation based on shared opinions, normative systems, and cultural reproduction.